Long-term seizure outcomes in patients with drug resistant epilepsy. (November 2018) - Conte, Francesca; Legros, Benjamin; Van Paesschen, Wim; Avbersek, Andreja; Muglia, Pierandrea; Depondt, Chantal
Highlights: Drug resistant epilepsy is a common problem, especially in tertiary referral centers. The proportion of patients that can be rendered seizure free is not well known. We show that over 60% of patients have ongoing seizures despite adequate treatment. Patients with ongoing seizures represent a severely affected population. There is an ongoing need for further development of novel treatments for epilepsy. Abstract: Purpose: Despite the availability of a broad range of treatments for epilepsy, a significant proportion of patients have ongoing seizures. This study aims to characterize the drug resistant population and to report long-term outcomes of patients undergoing different types of pharmacological and surgical treatment. Methods: Adult patients with drug resistant epilepsy (DRE) were identified from a largely retrospective database of 900 consecutive patients with epilepsy, recruited from two reference centers for DRE in Belgium. We report treatment trajectories and long-term seizure outcomes in the different treatment groups. Results: 640 patients had DRE. 249 (38.9%) underwent presurgical assessment, followed by surgical treatment in 197 (30.8%), resulting in seizure freedom in 86 (13.4%). 443 patients (69.2%) were treated only with further AED trials, of which 163 (25.5%) became seizure free. In the 391 patients with ongoing seizures (61.1%), mean age was 43.2 years, mean disease duration 23 years and mean number of AED trials 6.9. 291 (74.4%) had tonic-clonic seizures, and 43 (11.0%) had one or more episodes of status epilepticus. Patients with hippocampal sclerosis were significantly more likely to be seizure free, while patients with malformation of cortical development and those with temporal lobe epilepsy of unknown etiology were more likely to have ongoing seizures. Conclusion: Our findings demonstrate that – even with adequate access to surgical treatment and further AED trials – 61.1% of patients with DRE had ongoing seizures. This illustrates that there is a scope for ongoing development of novel treatments for DRE.